2017
DOI: 10.1080/23802359.2017.1318685
|View full text |Cite
|
Sign up to set email alerts
|

Leporinus elongatus(Characiformes, Anostomidae): complete mtDNA sequence of an economically important fish from the Paraná and La Plata river basins

Abstract: Leporinus elongatus is an important commercial fish found in the La Plata and Paraná River basins. Next-generation sequencing was used to sequence the mitochondrial DNA (mtDNA) of L . elongatus. The mtDNA was assembled using the CLC Workbench software v. 9.0 and subsequently aligned to other 10 complete fish mitochondrial sequences to enable phylogenetic analysis using MEGA 7.0. The complete mtDNA molecule had 16,784 bp and its GC content was 43%. The mt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…We estimated the topology using four calibration priors. The first was † Leporinus scalabrinii , an incomplete, articulated skull from the Ituzaingó Formation of the Late Miocene in Argentina (Bogan et al, 2012), hypothesized to be closer to Abramites Fowler 1906 (Bogan et al, 2012) and to have morphological affinities with Megaleporinus Ramirez, Birindelli & Galetti 2017 (Ramirez, Birindelli, Carvalho, et al, 2017), which in turn has three living species with available mitogenomes (Bedore et al, 2017; Yazbeck et al, 2016). This fossil prior included a lognormal distribution (offset = 6.0; mean = 3.0; SD = 1.0).…”
Section: Methodsmentioning
confidence: 99%
“…We estimated the topology using four calibration priors. The first was † Leporinus scalabrinii , an incomplete, articulated skull from the Ituzaingó Formation of the Late Miocene in Argentina (Bogan et al, 2012), hypothesized to be closer to Abramites Fowler 1906 (Bogan et al, 2012) and to have morphological affinities with Megaleporinus Ramirez, Birindelli & Galetti 2017 (Ramirez, Birindelli, Carvalho, et al, 2017), which in turn has three living species with available mitogenomes (Bedore et al, 2017; Yazbeck et al, 2016). This fossil prior included a lognormal distribution (offset = 6.0; mean = 3.0; SD = 1.0).…”
Section: Methodsmentioning
confidence: 99%
“…Studies of vertebrate species have shown a mutation rate that exceeds, by multiple times, nuclear DNA mutation rates that may be due to a lack of repair mechanisms during replication [116]. The complete mtDNA sequences have been sequenced to facilitate analyses of molecular markers in many economically important Neotropical fish species, such as S.brasiliensis [117], P. mesopotamicus [118] and L. elongatus [119].The DNA of cytoplasmic organelles has a non-Mendelian inheritance, and the mtDNA must be considered a single locus in genetic investigations [94]. Inheritance occurs via the mitochondria of the oocyte from which an animal develops [120].…”
mentioning
confidence: 99%